Asymmetric carbon nanotube hollow fiber membrane as well as preparation method and application thereof

By designing a carbon nanotube hollow fiber membrane with an asymmetric structure, the thickness of the separation layer is reduced and the crosslinking of polymers is achieved, the problems of poor structural strength and high preparation energy consumption are solved, and high permeability flux, good conductivity and strong anti-pollution performance are achieved.

CN119607906AActive Publication Date: 2025-03-14DALIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411772985.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing carbon nanotube hollow fiber membrane has poor structural strength and high preparation energy consumption, making it difficult to meet the needs of practical applications.

Method used

A hollow fiber membrane of asymmetric structure of carbon nanotubes is designed to increase the water permeability flux by reducing the thickness of the carbon nanotube separation layer, and adding the same polymer as the substrate to the spinning liquid of the separation layer, cross-linking between carbon nanotubes and carbon nanotubes and between carbon nanotubes and substrates is achieved to improve structural strength.

Benefits of technology

It achieves a thin separation layer, good conductivity and excellent permeability, good mechanical strength, and can be coupled with electrochemistry, which significantly improves the anti-pollution ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607906A_ABST
    Figure CN119607906A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric carbon nanotube hollow fiber membrane as well as a preparation method and application thereof, and belongs to the technical field of membrane method water treatment. The preparation method comprises the following steps: firstly, adding a carbon nanotube, a pore-forming agent and a high-molecular polymer into an organic solvent, uniformly dispersing, defoaming to obtain a separation layer spinning solution, adding the high-molecular polymer and the pore-forming agent into the organic solvent, dissolving, and defoaming to obtain a substrate spinning solution; and spinning the separation layer spinning solution serving as an outer shell solution, the substrate spinning solution serving as an inner shell solution and water serving as a core solution into a coagulating bath through a three-phase coaxial spinning head to obtain the asymmetric hollow fiber membrane of which the substrate is a high-molecular polymer and the separation layer is a carbon nanotube / high-molecular polymer. The prepared asymmetric carbon nanotube hollow fiber membrane has a thin separation layer, good conductivity and excellent permeation flux, the separation layer is in close contact with the substrate, the mechanical strength is good, electrochemistry can be coupled, and the anti-pollution capacity of the membrane is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane water treatment, and particularly relates to an asymmetric carbon nanotube hollow fiber membrane and a preparation method and application thereof. Background Art

[0002] Membrane separation technology is a relatively simple and low-energy separation process that uses the selective permeability of separation membranes to separate, concentrate and purify substances. At present, membrane separation technology has been widely used in drinking water purification, industrial wastewater treatment, food and beverage water sterilization, bioactive substance recovery and refinement, and has been rapidly promoted to many fields such as textiles, electricity, chemicals, petroleum, biology, and pharmaceuticals. Due to the limitations of their own materials and structures, traditional separation membranes still have many problems, such as membrane contamination, and the contradiction between selectivity and permeability.

[0003] Conductive separation membrane is a new type of separation membrane developed in recent years. It can couple electrochemical principles to improve its own performance and realize new functions that traditional separation membranes do not have. Studies have found that hollow fiber membranes based on carbon nanotubes have good conductivity and can achieve high-efficiency removal of small molecular pollutants in wastewater under high flux through electrically enhanced adsorption or electrooxidation decomposition (Environmental Science & Technology, 2014, 48, 8062-8068; ACS Applied Materials & Interfaces, 2015, 7, 14620-14627). Chinese invention patent ZL201310272800.4 discloses a method for preparing a carbon nanotube hollow fiber membrane based on electrophoretic deposition, but due to the thick membrane structure, the prepared membrane has a low permeation flux and a very low preparation efficiency; Chinese invention patent ZL201410079152.5 discloses a method for scalable preparation of carbon nanotube hollow fiber membranes, but the energy consumption is high and the prepared membrane structure strength is poor, which is difficult to meet the needs of practical applications. Therefore, it is of great value to develop new carbon nanotube hollow fiber membranes with excellent comprehensive performance and their efficient preparation methods. Summary of the invention

[0004] In view of the problems of poor structural strength and high energy consumption in preparation of existing nanotube hollow fiber membranes, the purpose of the present invention is to provide an asymmetric carbon nanotube hollow fiber membrane and an efficient preparation method thereof. The basic concept of the present invention is to design an asymmetric carbon nanotube hollow fiber membrane to reduce the thickness of the carbon nanotube separation layer, thereby reducing the water mass transfer resistance and increasing the water permeation flux; a high molecular polymer identical to that of the substrate is added to the separation layer spinning solution, and after phase inversion, the carbon nanotubes can be cross-linked with each other and with the substrate to achieve high structural strength; the separation layer spinning solution and the substrate spinning solution are simultaneously phase-inverted to prepare a carbon nanotube hollow fiber membrane with a substrate in one step, and the prepared asymmetric carbon nanotube hollow fiber membrane has a thinner separation layer, good conductivity and excellent permeation flux, and the separation layer is in close contact with the substrate, has good mechanical strength, and can be coupled with electrochemistry to significantly improve its own anti-pollution ability.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing an asymmetric carbon nanotube hollow fiber membrane, comprising the following steps:

[0007] (1) adding carbon nanotubes, a pore-forming agent, and a high molecular polymer into an organic solvent, stirring at a temperature of 30 to 80° C. until the carbon nanotubes are uniformly dispersed, and standing or vacuum degassing to obtain a separation layer spinning solution;

[0008] (2) adding a high molecular weight polymer and a pore-forming agent into an organic solvent, stirring at a temperature of 30 to 80° C. until dissolved, and allowing to stand or vacuum degas to obtain a base spinning solution;

[0009] (3) The separation layer spinning solution is used as the outer shell liquid, the base spinning solution is used as the inner shell liquid, and water is used as the core liquid. The spinning is simultaneously carried out through a three-phase coaxial spinning head into a coagulation bath at a temperature of 10 to 80°C to obtain an asymmetric hollow fiber membrane in which the base is a polymer and the separation layer is a carbon nanotube / polymer.

[0010] Based on the above technical solution, further, the carbon nanotubes described in step (1) include carbon nanotubes that have not been treated in any way, carboxyl carbon nanotubes, hydroxyl carbon nanotubes, amino carbon nanotubes and sulfonated carbon nanotubes, and the content of carboxyl, hydroxyl, amino and sulfonic acid groups on the surface of the carbon nanotubes is 0.5-10%.

[0011] Based on the above technical solution, further, the type of the carbon nanotubes in step (1) is single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture of two or more thereof.

[0012] Based on the above technical solution, further, the high molecular polymer described in step (1) and step (2) is one or a mixture of two or more of polyvinylidene fluoride, polyacrylonitrile, polyether sulfone, polysulfone, and polyvinyl butyral; the organic solvent is one or a mixed solvent of two or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0013] Based on the above technical solution, further, the pore-forming agent described in step (1) and step (2) is polyethylene glycol or polyvinyl pyrrolidone, preferably polyethylene glycol-400 or polyvinyl pyrrolidone K30.

[0014] Based on the above technical solution, further, the mass ratio of the high molecular polymer, pore-forming agent, carbon nanotubes and organic solvent in step (1) is (0.5-3):(0.1-1):1:(5-30), preferably (0.4-0.6):(0.1-1):1:(5-15).

[0015] Based on the above technical solution, further, the stirring time in step (1) is 1 to 3 days.

[0016] Based on the above technical solution, further, the mass ratio of the high molecular polymer, pore-forming agent and organic solvent in step (2) is 1:(0.1-1):(1-10), preferably 1:(0.4-0.6):1:(2-6).

[0017] Based on the above technical solution, further, in step (3), the flow rate ratio among the outer shell liquid, the inner shell liquid and the core liquid is 1:(1-5):(0.2-1), preferably 1:(1-1.5):(0.5-1).

[0018] Based on the above technical solution, further, the coagulation bath described in step (3) is a mixture of one or two of water and an organic solvent, the organic solvent is a mixed solvent of one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, and the volume ratio of water to the organic solvent is 1:(0~10).

[0019] In a second aspect, the present invention provides an asymmetric carbon nanotube hollow fiber membrane prepared by the above preparation method.

[0020] Based on the above technical solution, further, the cross section of the asymmetric carbon nanotube hollow fiber membrane is a layered structure, the separation layer is a mixture of carbon nanotubes and high molecular polymers, and the substrate is a high molecular polymer.

[0021] In a third aspect, the present invention provides application of the above-mentioned asymmetric carbon nanotube hollow fiber membrane in wastewater treatment.

[0022] Based on the above technical solution, further, the asymmetric carbon nanotube hollow fiber membrane is coupled with electrochemistry for wastewater treatment, with the asymmetric carbon nanotube hollow fiber membrane as the working electrode, a voltage of 0.5 to 3.0 V is applied between the working electrode and the counter electrode, and the filtration mode adopts a dead-end or cross-flow mode.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The asymmetric carbon nanotube hollow fiber membrane prepared by the present invention has high tensile strength, good flexibility, and can be bent and twisted.

[0025] (2) The asymmetric carbon nanotube hollow fiber membrane prepared by the present invention has high permeation flux and good separation performance.

[0026] (3) The asymmetric carbon nanotube hollow fiber membrane prepared by the present invention has good electrical conductivity, can couple the electrochemical principle, strengthen the electrostatic repulsion between the membrane surface and pollutants, and significantly improve the anti-pollution performance of the membrane.

[0027] (4) The preparation method of the asymmetric carbon nanotube hollow fiber membrane prepared by the present invention is simple and efficient, does not require expensive chemical reagents and equipment, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 Schematic diagram of the structure of the three-phase coaxial spinning head used in the embodiment;

[0030] Figure 2 This is a scanning electron microscope image of a cross section of an asymmetric carbon nanotube hollow fiber membrane prepared in Example 1;

[0031] Figure 3 This is a scanning electron microscope image of the surface of the asymmetric carbon nanotube hollow fiber membrane prepared in Example 1;

[0032] Figure 4 This is a scanning electron microscope image of the surface of the asymmetric carbon nanotube hollow fiber membrane prepared in Example 2;

[0033] Figure 5 It is a curve diagram showing the change of flux with the operation time when the asymmetric carbon nanotube hollow fiber membrane prepared in Example 1 of the application example is coupled with electrochemical filtration of electrophoretic coating wastewater;

[0034] Figure 6This is a curve chart showing the change in flux over the operating time when the asymmetric carbon nanotube hollow fiber membrane prepared in Example 1 is used alone to filter electrophoretic coating wastewater in Comparative Example 1.

[0035] Figure 7 This is a curve chart showing the change in flux versus operating time when the commercial membrane is used to filter electrophoretic coating wastewater in Comparative Example 2. DETAILED DESCRIPTION

[0036] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0037] Example 1

[0038] (1) Preparation of separation layer spinning solution: 3 g of carboxylated carbon nanotubes (carboxyl content of 2%) and 3.75 g of polyvinylidene fluoride were weighed and added to 39 g of N,N-dimethylacetamide in a mass ratio of 1:1.25:13, and 1.5 g of polyethylene glycol-400 was added as a pore-forming agent. The mixture was mechanically stirred at 60° C. for 48 h, and vacuum degassed to obtain a separation layer spinning solution.

[0039] (2) Preparation of base spinning solution: 9 g polyvinylidene fluoride and 3 g polyvinyl pyrrolidone K30 were weighed and added to N,N-dimethylacetamide in a mass ratio of 3:1:21, mechanically stirred at 60° C. for 12 h, and vacuum degassed to obtain a base layer spinning solution;

[0040] (3) Preparation of asymmetric carbon nanotube hollow fiber membrane: The three-phase coaxial wet spinning technology was used, with the separation layer spinning solution as the outer shell liquid, the base layer spinning solution as the inner shell liquid, and water as the core liquid. The spinning speed was 30 mL h -1 、30mL h -1 and 20mLh -1 The membrane was simultaneously spun into a 20°C water coagulation bath through a three-phase coaxial spinning head at a flow rate of 1.5 %. After spinning, the prepared membrane was soaked in water for 24 to 72 hours to remove the organic solvent and pore-forming agent, and then naturally dried and collected.

[0041] Figure 1 Schematic diagram of the structure of the three-phase coaxial spinning head used in the embodiment.

[0042] Figure 2 This is a scanning electron microscope image of the cross-section of the prepared carbon nanotube hollow fiber membrane. It can be seen from the figure that the membrane presents a typical layered structure. The inner layer is a polyvinylidene fluoride layer with a macroporous structure, and the outer layer is a carbon nanotube / polyvinylidene fluoride layer. The inner and outer layers are tightly combined.

[0043] Figure 3This is a scanning electron microscope image of the surface of the prepared carbon nanotube hollow fiber membrane. It can be seen from the image that the membrane surface is relatively smooth and has no defects such as cracks.

[0044] Example 2

[0045] (1) Preparation of separation layer spinning solution: 3 g of carboxylated carbon nanotubes (carboxyl content of 2.6%) and 2.25 g of polyvinylidene fluoride were weighed and added to 39 g of N,N-dimethylformamide in a mass ratio of 1:0.75:13, and 1.5 g of polyethylene glycol-400 was added as a pore-forming agent. The mixture was mechanically stirred at 60° C. for 48 h, and vacuum degassed to obtain a separation layer spinning solution.

[0046] (2) Preparation of base spinning solution: 9 g of polyvinylidene fluoride and 3 g of polyvinyl pyrrolidone K30 were weighed and added to N,N-dimethylformamide in a mass ratio of 3:1:21, and mechanically stirred at 60° C. for 12 h. After vacuum degassing, a base layer spinning solution was obtained;

[0047] (3) Preparation of asymmetric carbon nanotube hollow fiber membrane: The three-phase coaxial wet spinning technology was used, with the separation layer spinning solution as the outer shell liquid, the base layer spinning solution as the inner shell liquid, and water as the core liquid. The spinning speed was 30 mL h -1 、30mL h -1 and 20mLh -1 The membrane was simultaneously spun into a 20°C water coagulation bath through three coaxial spinning heads at a flow rate of 1.50 ℃. After spinning, the prepared membrane was soaked in water for 24 to 72 hours to remove the organic solvent and pore-forming agent, and then naturally dried and collected.

[0048] Figure 4 This is a scanning electron microscope image of the surface of the prepared carbon nanotube hollow fiber membrane. It can be seen from the figure that compared with the carbon nanotube hollow fiber membrane in Example 1, the surface of the membrane prepared in this example is rougher and has a large number of concave pore structures.

[0049] Example 3

[0050] (1) Preparation of separation layer spinning solution: 10 g of carboxylated multi-walled carbon nanotube powder (carboxyl content of 2.6%), 10 g of polyethersulfone powder and 5 g of polyvinylpyrrolidone K30 powder were weighed and added into 75 g of N-methylpyrrolidone, stirred at 60° C. for 24 h, and vacuum degassed to obtain a viscous spinning solution with a carbon nanotube mass fraction of 10%, wherein the mass ratio of carbon nanotube to polyethersulfone was 1:1;

[0051] (2) Preparation of base spinning solution: Weigh 5 g of polyethersulfone powder and 1 g of polyvinylpyrrolidone K30 powder and add them to 20 g of N-methylpyrrolidone, stir at 60° C. for 24 h to fully dissolve, and then vacuum or stand to degas to obtain the base layer spinning solution;

[0052] (3) Preparation of asymmetric carbon nanotube hollow fiber membrane: The three-phase coaxial dry-wet spinning technology was used. The separation layer spinning solution was used as the outer shell liquid, the base layer spinning solution was used as the inner shell liquid, and water was used as the core liquid. The spinning speed was 20 mL h -1 、30mL h -1 and 20 mL h -1 The asymmetric carbon nanotube hollow fiber membrane is immersed in water for 24 to 72 hours to remove the organic solvent and pore-forming agent, and then naturally dried and collected.

[0053] The prepared membrane has a uniform appearance, no obvious surface defects, and good hydrophilicity.

[0054] Example 4

[0055] (1) Preparation of separation layer spinning solution: 10 g of carboxylated multi-walled carbon nanotube powder (carboxyl content of 2%) and 5 g of polyvinyl pyrrolidone K30 powder were weighed and added to 75 g of N-methyl pyrrolidone, and stirred at room temperature for 12 h. Then, 10 g of polyacrylonitrile powder was added, and stirred at 80° C. for 24 h. After vacuum degassing, a separation layer spinning solution was obtained.

[0056] (2) Preparation of base spinning solution: Weigh 5 g of polyacrylonitrile powder and 2.5 g of polyvinyl pyrrolidone K30 powder and add them to 20 g of N-methylpyrrolidone, and stir at 60°C for 24 h to fully dissolve. Then, vacuum or stand degassing is performed to obtain the base layer spinning solution;

[0057] (3) Preparation of asymmetric carbon nanotube hollow fiber membrane: The three-phase coaxial wet spinning technology was used, with the separation layer spinning solution as the outer shell liquid, the base layer spinning solution as the inner shell liquid, and water as the core liquid. The spinning speed was 20 mL h -1 、30mL h -1 and 20 mL h -1 The flow rate is 200 μm, and the nanofibers are simultaneously spun into a coagulation bath of 60°C water and N-methylpyrrolidone through a three-phase coaxial spinning head, wherein the volume of water accounts for 40%. After the spinning is completed, the asymmetric carbon nanotube hollow fiber membrane is soaked in water for 24 to 72 hours to remove the organic solvent and pore-forming agent, and then naturally dried and collected.

[0058] Scanning electron microscopy showed that the prepared asymmetric carbon nanotube hollow fiber membrane had a uniform appearance, no obvious surface defects, and good hydrophilicity.

[0059] Application Examples

[0060] The asymmetric carbon nanotube hollow fiber membrane prepared in Example 1 was used as the anode, the titanium mesh was used as the cathode, the voltage between the anode and the cathode was set to 1.5 V, and the electrophoretic coating wastewater generated by a certain automobile company was filtered in a cross-flow mode, and the transmembrane pressure difference was set to 0.25 bar. Figure 5 As shown in the figure, during the 26 h operation, the membrane permeation rate increased from the initial 284 L m -2 h -1 bar -1 Gradually decrease to 130L m -2 h -1 bar -1 , the decline rate is about 54%.

[0061] Comparative Example 1

[0062] The asymmetric carbon nanotube hollow fiber membrane prepared in Example 1 was used to filter the electrophoretic coating wastewater generated by a certain automobile company in a cross-flow mode (same as in the application example), and the transmembrane pressure difference was set to 0.25 bar. Figure 6 As shown in the figure, during the 26 h operation, the membrane permeation rate increased from the initial 278 L m -2 h -1 bar -1 Gradually decrease to 90L m -2 h -1 bar -1 The decrease rate is about 68%, which is significantly higher than the flux decrease rate in the application example.

[0063] Comparative Example 2

[0064] The electrophoretic coating wastewater generated by an automobile company was filtered using a commercially purchased separation membrane in cross-flow mode (same as the application example), and the transmembrane pressure difference was set to 0.25 bar. The results are as follows Figure 7 As shown in the figure, during the 26-hour operation, the membrane permeation rate increased from the initial 91 Lm -2 h -1 bar -1 Gradually decrease to 25L m -2 h -1 bar -1 The decrease rate is about 73%, which is significantly higher than the flux decrease rate in the application example.

[0065] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing an asymmetric carbon nanotube hollow fiber membrane, characterized in that: The steps include: (1) adding carbon nanotubes, a pore-forming agent, and a high molecular polymer into an organic solvent, stirring at a temperature of 30 to 80° C. until the carbon nanotubes are uniformly dispersed, and standing or vacuum degassing to obtain a separation layer spinning solution; (2) adding a high molecular weight polymer and a pore-forming agent into an organic solvent, stirring at a temperature of 30 to 80° C. until dissolved, and allowing to stand or vacuum degas to obtain a base spinning solution; (3) The separation layer spinning solution is used as the outer shell liquid, the base spinning solution is used as the inner shell liquid, and water is used as the core liquid. The spinning is simultaneously carried out through a three-phase coaxial spinning head into a coagulation bath at a temperature of 10 to 80°C to obtain an asymmetric hollow fiber membrane in which the base is a polymer and the separation layer is a carbon nanotube / polymer.

2. The preparation method according to claim 1, characterized in that: The carbon nanotubes described in step (1) include carbon nanotubes that have not been treated in any way, carboxyl carbon nanotubes, hydroxyl carbon nanotubes, amino carbon nanotubes and sulfonated carbon nanotubes, and the content of carboxyl groups, hydroxyl groups, amino groups and sulfonic acid groups on the surface of the carbon nanotubes is 0.5-10%; the type of the carbon nanotubes is single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture of two or more thereof.

3. The preparation method according to claim 1, characterized in that: The high molecular polymer in step (1) and step (2) is one or a mixture of two or more of polyvinylidene fluoride, polyacrylonitrile, polyethersulfone, polysulfone, and polyvinyl butyral; the organic solvent is one or a mixture of two or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide; the pore-forming agent is polyethylene glycol or polyvinyl pyrrolidone, preferably polyethylene glycol-400 or polyvinyl pyrrolidone K30.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the high molecular polymer, pore former, carbon nanotube and organic solvent in step (1) is (0.5-3):(0.1-1):1:(5-30), preferably (0.4-0.6):(0.1-1):1:(5-15).

5. The preparation method according to claim 1, characterized in that: The mass ratio of the high molecular weight polymer, pore former and organic solvent in step (2) is 1:(0.1-1):(1-10), preferably 1:(0.4-0.6):1:(2-6).

6. The preparation method according to claim 1, characterized in that: In step (3), the flow rate ratio among the outer shell liquid, the inner shell liquid and the core liquid is 1:(1-5):(0.2-1), preferably 1:(1-1.5):(0.5-1).

7. The preparation method according to claim 1, characterized in that: The coagulation bath described in step (3) is a mixture of one or two of water and an organic solvent, the organic solvent is one or a mixed solvent of two or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, and the volume ratio of water to the organic solvent is 1:(0-10).

8. An asymmetric carbon nanotube hollow fiber membrane prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the asymmetric carbon nanotube hollow fiber membrane according to claim 8 in wastewater treatment.

10. The use according to claim 9, characterized in that: The asymmetric carbon nanotube hollow fiber membrane is coupled with electrochemistry for wastewater treatment, the asymmetric carbon nanotube hollow fiber membrane is used as a working electrode, a voltage of 0.5 to 3.0 V is applied between the working electrode and the counter electrode, and the filtration mode adopts a dead end or cross-flow mode.

Citation Information

Patent Citations

  • Preparation method of carbon-nanotube hollow fiber membranes

    CN103316594B

  • A method for the large-scale preparation of carbon nanotube hollow fiber membranes

    CN104028112B

  • Method for preparing hollow fiber composite membrane

    CN102228803A

  • Graphene hollow fiber membrane with carbon nanotube protection layer and preparation method of graphene hollow fiber membrane

    CN110215851A

  • Polymer hybrid ultrafiltration membrane and two-way spinning preparation method thereof

    CN112090293A